A Cinderella story - Rosman, Mark ((Philippines) : Warner Home Video, 2004)
Make believe gets a makeover. Substitute a cell phone for a glass slipper, a convertible for a two-door pumpkin, and an L.A. suburb for a kingdom for, far away and what do you get? A Happily ever-laughter twist on the Cinderella tale! Meet high school student Sam(Hilary Duff), who scrubs floors at a diner, copes with her wicked stepmother and stepsister, and all the while dreams of Princeton (the perfect spot for a would-be princess to find a prince). But maybe she has a Prince Charming already: her anonymous e-mail buddy ( Chad Michael Murray), who arranges to meet her at the Halloween dance. Sam panics when Mr. Anonymous turns out to be the coolest guy on campus. Can he love a girl who isn't part of the in crowd? Can fairy tale come true? Sure - but only if Sam stands up for herself and turns her dream into reality.